Propuesta de un instrumento de gestión ambiental correctivo-colectivo para la mejora de la gestión ambiental en la asociación de mineros artesanales del caserío igor - 2014. - Bazán Moya, Leslie Juliana (2015)
The following paper aims to propose an instrument of collective and corrective environmental management, to improve environmental management in artisanal mining activities. This way is expected to achieve the formalization of its members, also contributes to protecting the environment by proposing an environmental management plan that includes measures that will prevent, control and mitigate environmental impacts; in addition to designing environmental monitoring plan to track the environmental management tool. The study was developed in Huaranchal District, Otuzco Province, La Libertad Department. First we proceeded with the collection and analysis of data, visiting areas of activities for data collection in the field, review of environmental reports and interviewing the area members of influence in order to identify the significant environmental aspects, finally propose as a result the instrument of collective and corrective environmental management. The importance of this work is based on that throughout the description, characterization and analysis of physical, biological and social environment may identify environmental aspects, quantifying and assessing environmental impacts. Also then design and propose measures of prevention, correction, compensation and mitigation to ensure optimal environmental management by the association. From the results we can conclude that the implementation of the proposal will prevent and correct the environmental impacts caused by artisanal mining activities , and allows members of the association of miners formalized and resume their activities, avoiding a possible social conflict and therefore justifies the development of this project given its social, economic and environmental implications.